PENGARUH MODEL PEMBELAJARAN METAKOGNITIF TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 2 DELI TUA - Salsabila; Khairil Ansari (Jurnal Bastra (Bahasa dan Sastra), 2025)
The purpose of this study was to: (1) determine the ability to write explanatory texts of class VIII students of SMP Negeri 2 Deli Tua before using the Metacognitive learning model; (2) determine the ability to write explanatory texts of class VIII students after the Metacognitive learning model was applied; and (3) determine the effect of the Metacognitive learning model on the ability to write explanatory texts of class VIII students of SMP Negeri 2 Deli Tua. This study used a two-group test design and experimental methodology. The sample in this study consisted of 32 students from each control and experimental class, while the population used in this study consisted of all class VIII students at SMP Negeri 2 Deli Tua totaling 64 students. The researcher tested the analysis requirements, homogeneity test, and hypothesis test as part of the quantitative data analysis methodology to support this study. Based on the results of the study, the ability to write official letters of students before using the Metacognitive learning model had an average score of 62.1, which was in the sufficient range. Students who used the Metacognitive learning paradigm obtained an average score of 80.9, which was in the very good group. The provisions of ttable = 1.69726 and tcount = 5.398 are determined based on the results of the t-test conducted at a significance level of α = 0.05. Since tcount > ttable, or 5.398 > 1.69726, the alternative hypothesis, Ha, is accepted and the null hypothesis, H0, is rejected. Based on these results, it can be said that students of grade VIII of SMP Negeri 2 Deli Tua benefit from learning that utilizes the Metacognitive learning paradigm in terms of their capacity to create Explanatory Texts